Studies on transcription initiated by cauliflower mosaic virus 35S promoter from transgenic crops using fish cell lines (HINAE, YO‐K, RTG‐2) and rainbow trout Oncorhynchus mykiss. (2nd September 2013) - Kitagima, R.E.; Haga, Y.; Hirono, I.; Endo, M.; Satoh, S.
Abstract: Cauliflower mosaic virus 35S promoter (CaMV 35S) used in transgenic crops has been suspected to be active in animal cells. This study examined transfection of constructs for expression of green fluorescent protein (GFP), including CaMV 35S. Cytomegalovirus (CMV) promoter and promoterless constructs were used as positive and negative control, respectively. These constructs were transfected to kidney cells (YO‐K) and embryonic cells (HINAE) derived from Japanese flounder and gonad cells (RTG‐2) derived from rainbow trout. In addition, plasmid solution was injected intramuscularly into rainbow trout or offered by feed for consecutive 14 days to examine the distribution of GFP in tissues. GFP signal was detected in all treatments that used lipofection during transfection of plasmids into fish cell lines. CMV promoter induced a higher GFP expression in all cell types compared with CaMV 35S. The in vivo study showed that GFP controlled by CaMV 35S was only detected at the injection site, despite the huge number of copies injected. The CaMV 35S was only able to drive one‐third of GFP mRNA copies driven by CMV promoter. Administration of plasmid by feed was inefficient for transfection due to rapid degradation of plasmid DNA. DNA fragments (71 and 203 bp) derived from feed were detected in liver, kidney and spleen, while longer sequence (1224 bp) containing genetic information for GFP transcription was only detected in the gut until 24 h. CaMV 35S DNA fragment (203 bp) was detected until 48 h in kidney and spleen. The study showed that CaMV 35S was able to drive limited expression of GFP in fish cell lines and after intramuscular injection. Moreover, it was proposed that dietary DNA fragments, including the CaMV 35S sequence, were absorbed by the rainbow trout intestine but were cleaved into smaller fragments and consequently eliminated through metabolism or excretion.